1971
DOI: 10.1136/bjo.55.8.565
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculoma of the orbit and lacrimal gland.

Abstract: The three following cases of tuberculoma, one of the orbit and two of the lacrimal gland, are described because of their rarity (Offret, I939; Duke-Elder, I952). Case reportsThe three patients reported below were in good general condition, with no enlargement of the lymph glands, liver, or spleen. Apart from increased lymphocytes the blood count was normal. The urine was free from albumin and sugar. The blood pressure, pulse rate, and body temperature were normal. The faeces showed no parasitic ova. There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

1972
1972
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 1 publication
0
12
0
1
Order By: Relevance
“…The optic nerve or its sheath may be the source of infection; or a posterior tuberculous abscess of the cornea may cause disseminated infection requiring enucleation 7. Clinical presentation of intraocular tuberculosis includes subretinal abscess, granulomatous anterior uveitis with scleral perforation, exudative mass in anterior chamber, and choroidal mass with panuveitis 8…”
Section: Discussionmentioning
confidence: 99%
“…The optic nerve or its sheath may be the source of infection; or a posterior tuberculous abscess of the cornea may cause disseminated infection requiring enucleation 7. Clinical presentation of intraocular tuberculosis includes subretinal abscess, granulomatous anterior uveitis with scleral perforation, exudative mass in anterior chamber, and choroidal mass with panuveitis 8…”
Section: Discussionmentioning
confidence: 99%
“…Aggarwal et al reported 14 cases of eye involvement in tuberculosis from India; none of the cases had scrofuloderma, lacrimal gland involvement, bone erosion, or orbital abscess combined in a single case (5). Lacrimal gland involvement is more commonly seen in adult females in the age group of 35–50 years and is very rare in children (6).…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria may settle in the intraorbital region and cause periostitis of the orbital margin or tuberculoma of orbital tissue leading to proptosis (5). There can also be an extension to neighbouring structures such as paranasal sinuses, lacrimal gland and lacrimal sac (4,6). Cases of orbital tuberculoma may present as unilateral proptosis, as a unilateral partial or complete superior orbital fissure syndrome, or as an orbital apex syndrome (6).…”
Section: Discussionmentioning
confidence: 99%
“…Schmoll et al (2009) reported a 14-year-old Scottish teenager with tubercular dacryoadenitis with a rapidly-enlarging orbital mass. Isolated involvement of the lacrimal gland has also been described (Mortada et al 1971). It may be seen either in the form of lacrimal gland enlargement or abscesses.…”
Section: Case Reportmentioning
confidence: 97%